PERANCANGAN ALAT BANTU KERJA PENGOLESAN MINYAK NOX RUST PADA GEAR UNTUK MEMINIMALISIR WAKTU KERJA DI PT. HARAPAN CITRA JAYA - Pandiangan, Holipman; Sirait, Ganda (Computer Science and Industrial Engineering, 2022)
The design of Nox rust oil work tools aims to reduce lubrication time, minimize work time, increase production and reduce operator fatigue. In this study, we will use the Quality Function Deployment (QFD) method to design the tool by creating a House of Quality (HOQ). In the survey method, the investigator asked three questions about the problem that occurred and asked 11 questions (customer needs) to observe. This study uses the motion time measurement (MTM) method as a time measurement for the original and final design. As a result, (1) the design of the tapping tool is designed to improve productivity (2) the result of the tapping tool is designed to reduce fatigue (3) work time It is the result of the design of a tapping tool that is kept to a minimum.